2021
DOI: 10.3390/ijerph18042194
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Mobility on Long-Term Exposure to Ambient PM2.5: Assessing Effect Modification by Travel Patterns and Spatial Variability of PM2.5

Abstract: The impact of individuals’ mobility on the degree of error in estimates of exposure to ambient PM2.5 concentrations is increasingly reported in the literature. However, the degree to which accounting for mobility reduces error likely varies as a function of two related factors—individuals’ routine travel patterns and the local variations of air pollution fields. We investigated whether individuals’ routine travel patterns moderate the impact of mobility on individual long-term exposure assessment. Here, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…Taking most trips in the vicinities of home would likely attenuate the expected accuracy benefits from a dynamic exposure approach. This would confirm the previous hypothesis that states that daily exposures estimates obtained from the two approaches only differ substantially if an individual’s time spent away from home is large [ 21 , 93 95 ]. These findings, supported by the study by Yu et al [ 40 , 41 ] in China suggest that dynamic exposure assessment may only be warranted when studying those population groups that tend to spend more time in out-of-home activities in nonresidential neighborhoods and are thus exposed to considerable different conditions over the day.…”
Section: Discussionsupporting
confidence: 88%
“…Taking most trips in the vicinities of home would likely attenuate the expected accuracy benefits from a dynamic exposure approach. This would confirm the previous hypothesis that states that daily exposures estimates obtained from the two approaches only differ substantially if an individual’s time spent away from home is large [ 21 , 93 95 ]. These findings, supported by the study by Yu et al [ 40 , 41 ] in China suggest that dynamic exposure assessment may only be warranted when studying those population groups that tend to spend more time in out-of-home activities in nonresidential neighborhoods and are thus exposed to considerable different conditions over the day.…”
Section: Discussionsupporting
confidence: 88%
“…A census-based study in the United Kingdom found a lower difference between residential and a time-weighed work-home estimate (0.1 µg/m 3 ) despite having a similar range of exposures at the national level (2.3-21.8 µg/m 3 ), 28 as did a smaller regional study from the United States (0.03 µg/m 3 ; range = 1.25-16.58). 29 A study in Israel found that there was no difference in NO 2 exposures at work and home for a majority of the study sample 30 and a study by Yu et al 31 found that homebased exposure estimates in China were not substantially different from cell-phone tracked exposures at the population level. As stated by Dhondt, "detailed exposure models are of little use in public health if they cannot be used for assessing health impacts."…”
Section: Discussionmentioning
confidence: 96%
“… 4 , 42 Studies with time-activity surveys can inform models or datasets of varying complexity for predicting outcomes. 8 , 9 , 27 , 29 , 32 , 35 , 45 , 46 Review papers by Dias and Tchepel 4 and Steinle et al 34 summarize the different methods available and the data gaps in the field. Large, population-based cohorts like ours could be enhanced through modeling of ambient air pollution encountered throughout the day as increased complexity has been shown to reduce exposure misclassification.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Many research groups are currently developing and improving prediction models for exposure assessment in epidemiologic studies. However, most epidemiologic studies to date use air pollution predictions from a single model to assign exposures, although in recent years there have been additional efforts to develop statistical and computational exposure models with exhaustive datasets [ 21 , 22 ]. This is of critical importance because the results from these epidemiologic studies are often used to inform regulations, but the exposure–response functions that are generated from studies using different models for exposure assessment are not necessarily comparable, both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%